(untitled) (Semiárida, 2020)
The ranquel indians ("ranqueles") were an ethnic group of equestrian hunters and shepherds, who also gathered wild plants and practiced agriculture. Untll1879 they Iived in the present province of La Pampa and neighboring areas of the provinces of Córdoba and San Luis. At present small groups of rural settlers in the west of La Pampa preserve the practices and customs of their indigenous ancestors, and elder people remember other practices which are now obsolete. Their language, called chedungun is spoken only by few elder people and Is in its final phase of extinction. The ranquel are very familiar with both wild and cultived plants. In this paper a summarized account of the history, the main subsistence activities and the social organization of the ranquel are given, together with the outstanding features of the natural vegetation. Local names and uses of gathered and cultivated plants were recorded during the last 15 years by means of inquiries with qualified indian informants; 128 indian names corresponding to 129 botanical species are alphabetically Iisted. Their latin (scientific) and local spanish names, as well as uses of most of them, are also listed. It is also indicated if practices are traditional after verification with historical literature, and if the practices are still used among the rural people of the west of La Pampa. The meaning of the indian names is given.